Vasyuk Vladimir Leonidovich - Medical University, Staff of Bukovyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is devoted to the 60th anniversary of the orthopaedic surgeon the highest medical category, doctor of medical Sciences, Professor, head of chair of traumatology, orthopedics and neurosurgery Bukovina state medical University Vasyuk  Vladimir  Leonidovich.